Redesign Aplikasi Sekolah Berbasis Website Dengan Metode Design Thinking (Studi Kasus: Ezzi School) - Abednego Dwi Septiadi; Enjeli CIstia Sukmawati (Postgraduate, University of Mataram, 2025)
Administrative management in schools that are still manual is quite difficult, so it is necessary to adopt technology through a school information system. Ezzi School is a school information system application that makes it quite easy for administrators to manage administration. However, the appearance of the application still has a low level of user satisfaction, and the SUS score is 33, which is in the unacceptable category. Based on these problems, the researchers want to redesign the User Interface and User Experience to improve the user experience, so that the use of applications becomes more optimal. The research process was carried out using the Design Thinking method which has five stages, namely Empathize through interviews and questionnaires to identify needs, Define to define the main problem, Ideate through brainstorming to generate solution ideas, Prototype by making low-fidelity and high-fidelity wireframes developed in the form of a front end, and Testing using the System Usability Scale (SUS) method to measure the success rate of the redesign. The results show a score of 87 with grade scale A in the Excellent category, so this research has succeeded in improving user experience, and the design thinking method is effective in application redesign research.